ASSESSMENT OF CLIMACTERIC SYMPTOMS IN YOUNG WOMEN UNDERGOING CHEMOTHERAPY - Guimarães Neto, Antonio José; Vidal, Flávia Castello Branco (Cogitare Enfermagem, 2023)
Objective: To describe the prevalence of climacteric symptoms in women undergoing cancer treatment and to analyze its relationship with the number of chemotherapy cycles. Methods: Cross-sectional study with 47 women undergoing chemotherapy in two cancer reference hospitals in São Luís, Maranhão, Brazil, between March 2019 and July 2020. A structured questionnaire was used containing sociodemographic variables and information on menstrual function and symptoms. Bivariate analysis and binary logistic regression were performed to assess the relationship between predictor variables and number of chemotherapy cycles. Results: Mean age was 31.71 years, and amenorrhea and hot flushes were the most frequent symptoms, however, unrelated to the number of chemotherapy cycles. There was no association between the presence of climacteric effects and the type of chemotherapy (p=0.15). Conclusion: The results reaffirmed that chemotherapy can cause climacteric symptoms, thus emphasizing the need for measures to alleviate symptoms in patients facing this problem.